Case studies in Japanese negotiation behavior - Blaker, Michael; Giarra, Paul; Vogel, Ezra F. (Perspective series, 2002)
Explores four recent US-Japanese negotiations - two over trade and two over security-related issues - looking for patterns in Japan's approach and behaviour. Each study explains the cultural, as well as the political, institutional and personal factors, and assesses their influence.